Investigating the Influence of Methamphetamine on brain metabolism using 1H-MRS - Burger, Antoinette (Department of Psychiatry and Mental Health, 2016)
Methamphetamine (MA) has been shown to have a detrimental relationship with on neuronal integrity and viability, and has been associated with decreased executive function. The association of acute and short-term MA abstinence on brain metabolism, in adult MA abusers, is understudied. Negative relationships with brain metabolism, cognitive development and executive functioning in prenatally MA exposed children are reported, however these studies are limited. The aim of this study was to investigate the relationship between MA and brain metabolism in adults after acute and short-term abstinence. An additional aim was to investigate neurometabolite changes and relationship with general cognitive ability over time in prenatally MA exposed children.